2003
DOI: 10.1002/nme.782
|View full text |Cite
|
Sign up to set email alerts
|

Design sensitivity analysis and optimization for polymer sheet extrusion and mold filling processes

Abstract: SUMMARYA polymer processing design methodology is presented which can be used to improve the production of plastic components manufactured via extrusion and injection molding processes. The design method combines polymer process modelling, design sensitivity analysis and numerical optimization. It is applicable to systems with creeping ow of purely viscous non-Newtonian uids through thin cavities where the lubrication approximation may be applied. An analysis and an adjoint design sensitivity analysis are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…6,23,30 The specific die geometry used in this study is shown in Figure 3; it is symmetric about the die's centerline (i.e., x ¼ 0) and is similar to that presented elsewhere by Gifford. 13 It consists of four major regions, as shown in Figure 3: the manifold, preland, secondary manifold, and land.…”
Section: Coat-hanger Die Flow and Deformation Examplementioning
confidence: 98%
See 1 more Smart Citation
“…6,23,30 The specific die geometry used in this study is shown in Figure 3; it is symmetric about the die's centerline (i.e., x ¼ 0) and is similar to that presented elsewhere by Gifford. 13 It consists of four major regions, as shown in Figure 3: the manifold, preland, secondary manifold, and land.…”
Section: Coat-hanger Die Flow and Deformation Examplementioning
confidence: 98%
“…The Hele-Shaw model is widely employed in injection and compression molding 22 and has also been applied to sheet extrusion dies. 6,7,8,[23][24][25][26] On the basis of these assumptions, the mass and momentum conservation equations reduce to a single differential equation:…”
Section: Melt Flow Governing Equationmentioning
confidence: 99%
“…It is convenient to diagnose and modify designed before product manufacture for reducing cost and time, and lev-eling up quality. However, even though those modern computer-aided technologies as mentioned above play an important role in manufacture, the subject of how to determine optimal manufacturing parameters for extremely matching product required still exists [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Although there are a lot of methods such as statistical regression calculation, neural network model and genetic algorithm, grey relational analysis, and fuzzy theory etc.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (often referred to as 2.5 D) simulations provide a computationally efficient alternative to three-dimensional methods, while avoiding many of the simplifying assumptions and geometric restrictions of existing one-dimensional design equations (see, e.g., Refs. [15][16][17][18][19][20]. Sartor [15] was perhaps the first to combine numerical optimization with a two-dimensional flow network analysis to iteratively solve the die design problem using a powerlaw fluid model.…”
Section: Introductionmentioning
confidence: 99%
“…16 and 17, which greatly reduced the computational effort required in the design calculations. This approach was extended to dies having a uniform exit velocity and residence time; examples include coat-hanger dies [17] and dies with a general die cavity height distribution [19]. More recently, this die design approach was extended to address variability during operation [23].…”
Section: Introductionmentioning
confidence: 99%